Impact of including a slab effect into a 2D RC frame on the seismic fragility assessment: A comparative study - Arada, Ahmad Housam; Majid, Taksiah A.; Choong, Kok Keong (Open Engineering (Warsaw), 2025)
Seismic engineering typically uses 2D modelling techniques in seismic analysis due to their computational efficiency and simplicity. Compared with 3D models with high accuracy, 2D models might underestimate or overstate seismic responses. Therefore, this research compared the structural capacities and dynamic performance of 3D models and a set of equivalent 2D models. The objective was to examine the extent to which 2D models accurately represent 3D models. The study investigated two 3D RC frames with shear walls (5 and 10 stories) and two sets of equivalent 2D models. Initially, traditional 2D frames selected and extracted from 3D models were assessed and compared with the 3D models. Thereafter, 2D frames were designed with their equivalent slab strip and analysed and compared with the 3D models. All models were studied using (1) modal analysis, (2) pushover analysis, and (3) incremental dynamic analysis with eight far-field records. Furthermore, analytical fragility curves were derived for all models. Results showed that the 2D frame with a slab properly represented the 3D models in terms of plastic hinge formations, which led to a similar failure mechanism. Moreover, it exhibited greater compatibility with the 3D model regarding the shape and values of capacity and fragility curves.